2020
DOI: 10.1021/acs.jpcb.0c03281
|View full text |Cite
|
Sign up to set email alerts
|

Near-Quantitative Triplet State Population via Ultrafast Intersystem Crossing in Perbromoperylenediimide

Abstract: Perylenediimide (PDI) derivatives are essential organic semiconductor materials in a variety of photofunctional devices. By virtue of the large energy gap between the singlet and triplet excited states (ΔE ST = 1.1 eV), augmentation of the triplet state population in monomeric PDI is a challenging task. We report the metal atom-free approach in engendering a near-quantitative triplet yield in perbromoperylenediimide/octabromoperylenediimide (OBPDI), absorbing in the visible region of the electromagnetic spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 56 publications
8
70
0
Order By: Relevance
“…62 Broadly speaking, the more bromo atoms in a molecule, the faster the S 1 → T n and T 1 → S 0 processes, in line with the stronger heavy-atom enhanced SOC. 63 Unexpectedly, however, the S 1 → T n ISC for Br 4 NTE is noticeably slower than its less brominated analogues.…”
Section: Resultsmentioning
confidence: 96%
“…62 Broadly speaking, the more bromo atoms in a molecule, the faster the S 1 → T n and T 1 → S 0 processes, in line with the stronger heavy-atom enhanced SOC. 63 Unexpectedly, however, the S 1 → T n ISC for Br 4 NTE is noticeably slower than its less brominated analogues.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, for PBI-1 , the ISC rate or the triplet rise time is 8.2 ns, nearly identical to the 1 ICT* decay time (τ F = 8.1 ns). The brominated twisted PBI derivative and doubly phenanthrene-fused PBI derivatives were previously reported to have ultrafast ISC (0.38 or 0.25 ps). , In contrast, singly phenanthrene-fused PBI (τ ISC = 1 ns) and triply linked DIPBIs derivatives (τ ISC = 970 ps) showed ISC at a relatively slower timescale. , Thus, the ISC rate significantly varied (from few picoseconds to nanoseconds) in the different twisted derivatives having different extents of the π-conjugated framework.…”
Section: Resultsmentioning
confidence: 99%
“…The relatively slow time constants for the appearance of 3 *PDI are sufficient to discount singlet exciton fission as a triplet formation mechanism. Previous studies of rylene dye derivatives have shown intersystem crossing may results from the radical pair (RP-ISC) or spin–orbit charge-transfer (SOCT-ISC) mechanisms. However, in p- PDI 2 and m- PDI 2 , there is no direct evidence for ion pair state formation, so that RP-ISC and SOCT-ISC are not operative here. The PDI chromophores in p- PDI 2 and m- PDI 2 have far more conformational freedom about the single bonds joining them to their phenylene spacers than does o- PDI 2 .…”
Section: Resultsmentioning
confidence: 99%